A novel method of treament of ascending aortic aneurysm - V.B. Demyanchuk; V.V. Pogrebnyak; O.I. Kvasha; B.M. Todurov (Кардіохірургія та інтервенційна кардіологія)
The need for surgical treatment of ascending aortic aneurysms is due to a number of severe complications that occur during the natural course of the disease, such as aortic dissection and rupture. Such interventions show good immediate and long-term treatment outcomes, but they are often accompanied by high blood loss and surgical trauma, which in elderly patients with concomitant pathology can lead to serious cardiac and extracardiac complications and prolongation of treatment in general. We present a technology of external wrapping of the aorta that reduces surgical trauma while maintaining effect of operation. A clinical case of application of this technology in a 63-year-old patient hospitalized to the clinic of the Heart Institute, Ministry of Health of Ukraine, with a diagnosis of aortic insufficiency of the 3rd degree (tricuspid aortic valve), dilatation of the root and ascending aorta, tricuspid insufficiency of the 2nd degree, high pulmonary hypertension, heart failure with reduced left ventricular systolic function. The use of the proposed method has following advantages compared to the established method of fixation of the vascular prosthesis: fixation of the proximal part of the vascular prosthesis is performed using vascular suture material; elimination of the risk of damage to the aortic wall; elimination of the risk of massive bleeding from the aorta at the site of the prosthesis fixation; decreased duration of surgery.